Pendekatan Daya Tarik Destinasi Dalam Pengelolaan Desa - Junaidi, Ilham; Ang, Gavrilla Kezia (Program Studi Pariwisata Program Sarjana, Fakultas Pariwisata, Universitas Udayana, 2023)
There is limited literature that examines villages in the perspective of destination attractiveness. The purpose of this research is to 1) describe the tourism potential of the village; 2) analyse the role of stakeholders in promoting the village as a tourism destination; 3) describe the steps or efforts to develop the village as a tourism destination from the perspective of destination attractiveness. A qualitative approach guides the author in analysing the attractiveness of destinations in Hila village. Data collection was carried out through interviews, observation and literature studies in April 2022. The results showed that Hila village has natural and cultural potential to become a destination product. However, local stakeholders tend to only focus on Amsterdam as a rural tourism icon. Local organisation (Pokdarwis) as rural tourism manager faces challenges in carrying out the duties and roles of destination managers, including integrating elements of destination attractiveness. This study outlines the urgency of destination attractiveness in managing it as a tourism destination. This research contributes to strengthening the concept of destination attractiveness as a strategy for managing natural and cultural potential through packaging potential into tourism destination products. Destination attractiveness can be an effective strategy if Pokdarwis, the government and the community become integral to developing rural tourism. This research fills in the tourism literature on analysing tourist villages and implementing practical steps for managing destinations from the perspective of destination attractiveness. Keywords: Destination attractiveness; Hila village; tourism village; village management; tourism stakeholder